Estimation method of adhesive force between separator and electrode
A correlation equation using weight and thickness of the separator's coating layer allows non-destructive, real-time estimation of adhesion force between the separator and electrode, addressing the limitations of existing destructive testing methods and improving manufacturing consistency.
Patent Information
- Application Number
- KR1020210123733
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-16
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2041-09-16
AI Technical Summary
Existing methods for measuring the adhesion force between a separator and an electrode in a battery are destructive, limited to partial samples, and cannot be performed in real time, making it difficult to ensure consistent adhesion across the entire electrode assembly.
A method using a correlation equation based on the weight and thickness of the separator's coating layer to estimate adhesion force without destructive testing, allowing real-time assessment on the entire electrode assembly.
Enables non-destructive, real-time estimation of adhesion force with high reliability, reducing battery defects by ensuring consistent adhesion throughout the manufacturing process.
Smart Images

Figure 112021107428313-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for estimating the adhesion force between a separator and an electrode. Specifically, it relates to a method for estimating the adhesion force between a separator and an electrode in a battery using other physical property values without directly measuring the adhesion force. Background Technology
[0002] A battery may be composed of an electrode assembly consisting of a positive electrode, a negative electrode, and a separator, and an electrolyte. It is important that the separator electrically insulates the positive electrode and the negative electrode to prevent short circuits, while ensuring ion conductivity by allowing ions to pass through based on high porosity.
[0003] Characteristics required for battery separators include excellent air permeability, low thermal shrinkage, and high puncture strength. When manufacturing an electrode assembly by laminating the electrode and the separator, it is also important to have sufficient adhesion to prevent the electrode and the separator from each other.
[0004] If the adhesion between the separator and the electrode is insufficient, the separator and the electrode may separate. Ionic conductivity drops sharply in the area where the separator and the electrode are separated, and inorganic materials detached from the separator during this separation process can induce localized defects.
[0005] A separator used in a battery may be composed of a separator substrate having a porous structure made of a polyolefin-based material, and a coating layer formed on the separator substrate to provide additional functions. In the case of a lithium secondary battery, the coating layer often contains inorganic materials, which can suppress shrinkage of the separator due to temperature.
[0006] The adhesion between the separator and the electrode is presumed to be influenced by the electrode—specifically, by materials such as the active material and binder used in the electrode active layer—and by the inorganic materials and binder used in the separator coating layer. Additionally, it is predicted that the microscopic physical morphology at the interface where the separator and the electrode contact each other will also have an influence. To date, no technology has been provided for a method to estimate the adhesion between the separator and the electrode based on these chemical characteristics and microscopic data.
[0007] To accurately measure the adhesion between the separator and the electrode, the most accurate method is to manufacture a separate test specimen and measure the peel strength. However, due to the nature of the continuous battery assembly process, this method has the problem that 1) it can only be performed on a portion of the electrode assembly samples, 2) it is performed in the form of an irreversible destructive test, and 3) it cannot be performed in real time.
[0008] Furthermore, measuring only the adhesion to the intermediate layer in a state where multiple electrodes and separators are stacked in the form of an electrode assembly is an even more difficult task.
[0009] Patent Document 1 relates to a method for measuring the adhesion of a separator used in a secondary battery, and describes a method for measuring the adhesion of a separator having a porous coating layer in which a plurality of inorganic particles are connected and fixed to each other by a binder polymer on a polymer substrate.
[0010] Patent Document 1 relates to a direct measurement method in which an adhesive tape is attached to and peeled off on the surface of a porous coating layer of a separator to analyze the adhesive strength, and also relates to a method for measuring the adhesive strength between a separator substrate and a coating layer.
[0011] Patent Document 2 relates to a method for measuring binder distribution within an electrode, wherein the adhesive strength of each is measured while removing the electrode active material layer and the current collector from the electrode using tape, and thereby the binder distribution within the electrode is measured.
[0012] Patent Document 2 cannot be applied to the problem to be solved by the present invention in that it measures the internal binder distribution using a tape as a method for measuring the composition within the electrode.
[0013] Patent Document 3 relates to a separation membrane comprising a porous coating layer formed from a mixture of a plurality of inorganic particles and a binder polymer on a porous substrate, and is a technology that aims to improve the adhesion between the coating layer and the porous substrate by using a novel binder.
[0014] Patent document 4 relates to a polyolefin microporous membrane characterized by the slope a of the approximation y=ax+b, which is required by linear regression of the melting peak temperature value observed by changing the heating rate on an xy plane where the melting peak temperature observed by differential scanning calorimetry is on the y-axis and the natural logarithm of the heating rate is on the x-axis, being 2.5 or greater and 3.2 or less. It provides a polyolefin microporous membrane with excellent hot box characteristics.
[0015] Patent Document 5 describes a method for measuring the deformation distribution of an adhesive in an adhesive strength test and calculating the elastic properties of the adhesive using the deformation distribution, but it cannot be a solution to the problem required by the present invention.
[0016] A technology that can measure or estimate the adhesion between the separator and the electrode in this way, 1) be performed on the entire sample of the electrode assembly, 2) be performed in a non-destructive testing manner so as not to affect the manufactured product, and 3) be performed in real time, has not been presented yet. Prior art literature
[0017] Republic of Korea Published Patent Application No. 2019-0056781 ('Patent Document 1') Republic of Korea Registered Patent Application No. 1982571 ('Patent Document 2') Republic of Korea Published Patent Application No. 2011-0104791 ('Patent Document 3') Japanese Published Patent Application No. 2021-014572 ('Patent Document 4') Japanese Published Patent Application No. 2020-106378 ('Patent Document 5') The problem to be solved
[0018] The present invention aims to solve the above-mentioned problem by providing a method that can measure or estimate the adhesion force between the separator and the electrode without manufacturing the separator and the electrode as separate test specimens.
[0019] The present invention also aims to provide a method for measuring or estimating the adhesion between a separator and an electrode that 1) can be performed on an entire sample of an electrode assembly, 2) can be performed in the form of a non-destructive inspection so as not to affect the product being manufactured, and 3) can be performed in real time. means of solving the problem
[0020] To solve the above-mentioned problems, the present invention comprises (S1) a step of measuring X and Y in a separator,
[0021] (S2) A method for estimating the adhesion between a separator and an electrode using a correlation equation of X, Y, and the adhesion between the separator and the electrode, wherein X is the weight of the coating layer alone per unit area of the separator and Y is the thickness of the coating layer alone of the separator.
[0022] Measuring X and Y in the above-mentioned membrane can be derived by measuring the weight and thickness of the entire membrane including the coating layer, and measuring the weight and thickness of the membrane from which the coating layer has been removed, and using the difference between them.
[0023] The above separator is a separator comprising a separator substrate having a porous structure including a polyolefin-based material and a coating layer including an inorganic material formed on at least one surface of the separator substrate, and the electrode is an anode or a cathode.
[0024] After the above step (S2), (S3) a step of determining whether there is an adhesion defect between the separator and the electrode using the adhesion force between the separator and the electrode estimated in the above step (S2) may be added.
[0025] Prior to the above step (S2), a calibration may be performed comprising: (S0-1) a step of measuring the adhesion between the separator and the electrode, the adhesion force to be estimated, the X, and the Y; and (S0-2) a step of deriving a correlation equation between the X, the Y, and the adhesion force between the separator and the electrode through multiple regression analysis. The calibration may be performed periodically or intermittently, and the additional calibration data may replace the conventional calibration data or be added to the conventional calibration data.
[0026] Measuring the adhesion between the separator and the electrode may involve peeling the separator and the electrode at a 180-degree angle and measuring the peel strength.
[0027] The above correlation equation can be applied in the range where the value of the thickness of the coating layer alone (Y) in the separator and the thickness of the separator excluding the coating layer (A) in the separator is 0.6 to 0.8, and X / Y (g / cm³) is 1.4 to 1.8.
[0028] In addition, the above correlation equation can be applied to a range of ±0.1 from the center value of the thickness of the coating layer alone (Y) in the separator and the thickness of the separator excluding the coating layer (A) in the separator, and a range of ±0.2 from the center value of X / Y (g / cm³).
[0029] The above correlation equation is: Adhesion force between the separator and the electrode = A0 + A1*X + B1*Y + A2*X 2 + B2*Y 2 + C1*X*Y, where parameters A0, A1, B1, A2, B2, and C1 may be derived through multiple regression analysis with X and Y as independent variables and the adhesion force between the separator and the electrode as the dependent variable.
[0030] The above correlation equation is newly derived whenever the separator is changed or the electrode is changed, and can be applied when the correlation is 0.8 or higher.
[0031] The present invention can also be provided in a form that combines various means for solving the above problem. Effects of the invention
[0032] As explained above, the present invention can estimate the adhesion between the separator and the electrode without disassembling the electrode assembly by using only X, which is the weight of the coating layer alone per unit area of the separator, and Y, which is the thickness of the coating layer alone of the separator. In particular, the correlation between X, Y, and the adhesion between the separator and the electrode is high at 0.8 or higher, indicating that the reliability of the estimation method according to the present invention is high.
[0033] The present invention has the advantage of being able to measure or estimate the adhesion force between the separator and the electrode without manufacturing the separator and the electrode as separate test specimens.
[0034] The present invention also has the advantages of 1) being able to be performed on all samples of the electrode assembly, 2) being performed in a non-destructive inspection form so as not to affect the manufactured product, and 3) being able to be performed in real time, thereby allowing for immediate feedback to be used for process Q / C, which has the advantage of reducing the battery defect rate in the entire process. Brief explanation of the drawing
[0035] FIG. 1 is a step of a method for estimating the adhesion force between a separator and an electrode according to one embodiment of the present invention. Figure 2 shows the distribution of data according to one embodiment of the present invention according to conditional expression (1). Figure 3 shows the distribution of data according to one embodiment of the present invention according to conditional expression (2). Figure 4 is the result of a multiple regression analysis on the adhesion force between a separator and an electrode according to one embodiment of the present invention. Specific details for implementing the invention
[0036] Embodiments that enable a person skilled in the art to easily practice the present invention are described in detail below with reference to the attached drawings. However, in describing the operating principles of preferred embodiments of the present invention in detail, if it is determined that a specific description of related known functions or configurations may unnecessarily obscure the essence of the present invention, such detailed description is omitted.
[0037] In addition, the same reference numerals are used for parts having similar functions and operations throughout the drawings. Throughout the specification, when a part is described as being connected to another part, this includes not only cases where they are directly connected, but also cases where they are indirectly connected with other elements in between. Furthermore, unless specifically stated otherwise, the inclusion of a certain component does not exclude other components but implies that additional components may be included.
[0038] Furthermore, descriptions that specify components by limiting or adding them may be applied to all inventions unless specifically limited, and are not limited to descriptions of specific inventions.
[0039] In addition, throughout the description of the invention and claims of this application, items indicated in the singular include cases where they are plural unless otherwise noted.
[0040] In addition, throughout the description of the invention and the claims of the present invention, "or" includes "and" unless otherwise noted. Therefore, "comprising A or B" means all three of the above cases: including A, including B, or including both A and B.
[0041] In addition, all numerical ranges include the values at both ends and all intermediate values in between, unless explicitly stated to be excluded.
[0042] The present invention is described in detail with reference to the drawings and embodiments.
[0043] FIG. 1 is a step of a method for estimating the adhesion force between a separator and an electrode according to one embodiment of the present invention.
[0044] Referring to FIG. 1, the present invention comprises (S1) a step of measuring X and Y in a separator, and (S2) a step of estimating the adhesion force (Z') between the separator and the electrode using the correlation equation of the X, the Y, and the adhesion force between the separator and the electrode, wherein X is the weight of the coating layer alone per unit area in the separator, and Y is the thickness of the coating layer alone in the separator.
[0045] Measuring X and Y in the above-mentioned separator involves measuring the weight and thickness of the entire separator including the coating layer, and measuring the weight and thickness of the separator with the coating layer removed, and deriving them using the difference.
[0046] The above separator is a separator comprising a separator substrate having a porous structure including a polyolefin-based material and a coating layer including an inorganic material formed on at least one surface of the separator substrate, and the electrode is an anode or a cathode.
[0047] After the above step (S2), (S3) a step of determining whether there is an adhesion defect between the separator and the electrode using the adhesion force between the separator and the electrode estimated in the above step (S2) is added.
[0048] Prior to the above step (S2), a calibration may be performed comprising the steps of: (S0-1) measuring the adhesion force (Z) between the separator and the electrode, X, and Y, for which the adhesion force is to be estimated; and (S0-2) deriving a correlation equation between X, Y, and the adhesion force between the separator and the electrode through multiple regression analysis. The calibration may be performed periodically or intermittently, and the additional calibration data may replace the conventional calibration data or be added to the conventional calibration data. In FIG. 1, the additional calibration is indicated by the arrow on the left.
[0049] Meanwhile, to perform the multiple regression analysis in step (S0-2) above, a process may be added to select a range in which the value of the thickness of the coating layer alone (Y) in the separator and the thickness of the separator excluding the coating layer (A) is 0.6 to 0.8 and X / Y (g / cm³) is 1.4 to 1.8, or to select only the range of ±0.1 from the center value of the thickness of the coating layer alone (Y) in the separator and the thickness of the separator excluding the coating layer (A) in the separator, and ±0.2 from the center value of X / Y (g / cm³), thereby selecting a set of {X, Y, Z} measurement values corresponding thereto. According to an embodiment of the present invention, a high correlation was found for the above ranges.
[0050] Meanwhile, measuring the adhesion between the separator and the electrode may involve peeling the separator and the electrode at a 180-degree angle and measuring the peel strength.
[0051] The above correlation equation is: Adhesion force between the separator and the electrode = A0 + A1*X + B1*Y + A2*X 2 + B2*Y 2 + C1*X*Y, where parameters A0, A1, B1, A2, B2, and C1 may be derived through multiple regression analysis with X and Y as independent variables and the adhesion force between the separator and the electrode as the dependent variable.
[0052] The above correlation equation is newly derived whenever the separator is changed or the electrode is changed, and can be applied when the correlation is 0.8 or higher.
[0053] (Separator)
[0054] The above separator is interposed between the anode and the cathode, and an insulating thin film having high ion permeability and mechanical strength is used. The pore diameter of the separator is generally 0.01 μm to 10 μm, and the thickness is generally 5 μm to 300 μm.
[0055] The battery separator of the present invention comprises a separator substrate having a porous structure and comprising a polyolefin-based or polymer resin, and a coating layer comprising an inorganic material formed on at least one surface of the separator substrate.
[0056] The above-mentioned separator substrate may be composed of one or more selected from the group consisting of, for example, high-density polyethylene, low-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenyleneoxide, polyphenylenesulfidro, polyethylenenaphthalene, and mixtures thereof.
[0057] The above-mentioned separator substrate can be manufactured by uniaxial or biaxial stretching, and the separator stretched in this way can shrink back to its original size when the temperature increases.
[0058] When using a material with high thermal shrinkage properties like this, if the separator shrinks during the use of the lithium secondary battery, contact between the positive and negative electrodes may occur, potentially leading to an internal short circuit.
[0059] The present invention comprises a coating layer comprising an inorganic material formed on at least one surface of a separator substrate. The coating layer comprising the inorganic material is an inorganic layer comprising an inorganic material and a binder. Typically, an effect of improving heat resistance can be obtained by using a double-sided coated separator in which an inorganic layer is formed on both sides of the separator substrate.
[0060] The above inorganic layer may include inorganic materials and a binder, and the binder may maintain the bonding between inorganic particles and improve the adhesion between the electrode and the separator.
[0061] The type of such binder is not particularly limited as long as it does not cause chemical changes to the separator coating layer, and includes, for example, polyolefins such as polyethylene and polypropylene; fluorine-containing resins such as polyvinylidene fluoride and polytetrafluoroethylene; fluorine-containing rubbers such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer; styrene-butadiene copolymer and its hydride; (meth)acrylic acid ester copolymers such as methacrylic acid ester copolymer, acrylonitrile acrylic acid ester copolymer, and styrene acrylic acid ester copolymer; rubbers such as ethylene propylene rubber; polyvinyl acetate; It may be one or more selected from the group consisting of polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamide, polyimide, polyamideimide, polyetheramide, polyester, aromatic polyester, and polyetheretherketone, which have a melting point or glass transition temperature of 180°C or higher; polycarbonate; polyacetal; and water-soluble resins such as carboxyalkylcellulose, alkylcellulose, hydroxyalkylcellulose, starch, polyvinyl alcohol, sodium alginate, polyethylene glycol, cellulose ester, polyacrylic acid, polyacrylamide, and polymethacrylic acid, and tannic acid.
[0062] The inorganic materials constituting the above inorganic layer are BaTiO3, Pb(Zr,Ti)O3(PZT), and Pb 1-x La x Zr 1-y Ti y O3(PLZT) (0 <x<1, 0<y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), hafnia(HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y(PO4)3, 0 <x<2, 0<y<3), (LiAlTiP) x O y Series glass (0 <x<4, 0<y<13), 리튬게르마늄티오포스페이트(Li x Ge y P z S w , 0 <x<4, 0<y<1, 0<z<1, 0<w<5), 리튬나이트라이드(Li x N y , 0 <x<4, 0<y<2), SiS2계열 glass(Li x Si y S z , 0 <x<3, 0<y<2, 0<z<4), P2S5계열 glass (Li x P y S z , 0 <x<3, 0<y<3, 0<z<7) 및 이들의 혼합체로 이루어진 군으로부터 선택된 하나 이상일 수 있지만, 이들만으로 한정되는 것은 아니다.
[0063] The coating method of the above-mentioned inorganic layer is not particularly limited, and conventional coating methods known in the art may be used. For example, various methods such as dip coating, die coating, roll coating, comma coating, spin coating, spray coating, or a combination thereof may be used.
[0064] Regarding the adhesion force between the above-mentioned separator and the above-mentioned electrode, the above-mentioned electrode may be an anode or a cathode.
[0065] (anode)
[0066] The above anode is manufactured, for example, by applying an anode composite containing an anode active material onto an anode current collector and then drying it, and the anode composite may optionally further include a binder, a conductive material, a filler, etc., as needed.
[0067] The above positive current collector is generally made with a thickness of 3 μm to 500 μm. Such a positive current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive current collector may have fine irregularities formed on its surface to increase the adhesion of the positive active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible.
[0068] The above-mentioned positive electrode active material is a material capable of causing an electrochemical reaction, and is a lithium transition metal oxide comprising two or more transition metals, for example, Li 1+z Ni b Mn c Co 1-(b+c+d) M d O (2-e) A e A lithium nickel cobalt manganese composite oxide represented by (where -0.5≤z≤0.5, 0.1≤b≤0.8, 0.1≤c≤0.8, 0≤d≤0.2, 0≤e≤0.2, b+c+d<1, M = Al, Mg, Cr, Ti, Si, or Y, and A = F, P, or Cl); chemical formula Li 1+x M 1-y M' y PO 4-z X z Examples include olivine-based lithium metal phosphates expressed as (where M = transition metal, preferably Fe, Mn, Co, or Ni, M' = Al, Mg, or Ti, X = F, S, or N, and -0.5≤x≤+0.5, 0≤y≤0.5, 0≤z≤0.1), but are not limited to these.
[0069] The above conductive material is typically added in an amount of 1% to 30% by weight based on the total weight of the mixture containing the positive electrode active material. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives or carbon nanotubes may be used.
[0070] The above binder is a component that assists in the bonding of the active material and the conductive material, and in the bonding to the current collector, and is typically added in an amount of 1% to 30% by weight based on the total weight of the mixture containing the positive active material. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butylene rubber, fluororubber, or various copolymers.
[0071] The above-mentioned filler is optionally used as a component to inhibit the expansion of the electrode, and is not particularly limited as long as it is a fibrous material that does not cause chemical changes in the battery; for example, olivine-based polymers such as polyethylene and polypropylene; and fibrous materials such as glass fibers and carbon fibers are used.
[0072] (cathode)
[0073] The above cathode is manufactured, for example, by applying a cathode composite containing a cathode active material onto a cathode current collector and then drying it, and the cathode composite may include, if necessary, components such as a conductive material, a binder, and a filler as described above.
[0074] The above negative current collector is generally made with a thickness of 3 μm to 500 μm. Such a negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, similar to the positive current collector, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative active material, and it may be used in various forms such as film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0075] The above-mentioned cathode active material is, for example, carbon such as non-graphitizable carbon, graphite-based carbon, etc.; Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, 2, and 3 elements of the periodic table, halogens; 0 <x≤1; 1≤y≤3; 1≤z≤8) 등의 금속 복합 산화물; 리튬 금속; 리튬 합금; 규소계 합금; 주석계 합금; SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5등의 금속 산화물; 폴리아세틸렌 등의 도전성 고분자; Li-Co-Ni 계 재료 등을 사용할 수 있다.
[0076] The above binder, conductive material, and optionally added components are the same as those described for the anode.
[0077] In addition, other components such as viscosity modifiers and adhesion promoters may be optionally included or in combination of two or more.
[0078] The above viscosity modifier is a component that controls the viscosity of the electrode mixture to facilitate the mixing process of the electrode mixture and the coating process on the current collector, and can be added up to 30 weight percent based on the total weight of the cathode mixture. Examples of such viscosity modifiers include carboxymethylcellulose and polyvinylidene fluoride, but are not limited to these. In some cases, the solvent described above may also serve as a viscosity modifier.
[0079] The above adhesion promoter is an auxiliary component added to improve the adhesion of the active material to the current collector, and can be added in an amount of 10 weight% or less relative to the binder, and examples include oxalic acid, adipic acid, formic acid, acrylic acid derivatives, itaconic acid derivatives, etc.
[0080] The present invention also provides a battery cell comprising an electrode assembly manufactured by using an estimation method according to the present invention to verify the adhesion between the separator and the electrode, and thereby selecting an electrode assembly with defects.
[0081] The present invention provides a battery cell comprising an electrode assembly having the above-described separator for a lithium secondary battery interposed between a positive electrode and a negative electrode, and the battery cell may be a lithium secondary battery having a structure in which the electrode assembly is impregnated in a lithium salt-containing non-aqueous electrolyte.
[0082] The above lithium secondary battery may be a pouch-type secondary battery, a cylindrical-type secondary battery, or a prismatic-type secondary battery depending on the shape of the battery case.
[0083] (Electrolytes)
[0084] The above lithium salt-containing non-aqueous electrolyte consists of an electrolyte and a lithium salt, and the electrolyte used is a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc.
[0085] As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butylolactone, 1,2-dimethoxyethane, tetrahydroxyfranc, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc. may be used.
[0086] The above organic solid electrolyte may be, for example, a polyethylene derivative, a polyethylene oxide derivative, a polypropylene oxide derivative, a phosphate ester polymer, agitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, a polymer containing an ionic dissociator, etc.
[0087] As the above-mentioned inorganic solid electrolyte, for example, nitrides, halides, sulfates of Li such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, etc., may be used.
[0088] The above lithium salt is a substance that dissolves well in the above-mentioned non-aqueous electrolyte, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, imide, etc. may be used.
[0089] In addition, for the purpose of improving charge / discharge characteristics and flame retardancy, the electrolyte may be further enriched with, for example, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphate triamide, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, to impart non-flammability, halogen-containing solvents such as carbon tetrachloride and trifluoroethylene may be further enriched, carbon dioxide may be further enriched to improve high-temperature storage characteristics, and FEC (Fluoro-Ethylene Carbonate), PRS (Propene Sultone), etc.
[0090] In one preferred example, a lithium salt-containing non-aqueous electrolyte can be prepared by adding a lithium salt such as LiPF6, LiClO4, LiBF4, LiN(SO2CF3)2 to a mixed solvent of a cyclic carbonate of a high dielectric solvent such as EC or PC and a linear carbonate of a low viscosity solvent such as DEC, DMC, or EMC.
[0091] (Device)
[0092] The present invention also provides a battery pack comprising the secondary battery as a unit cell, and a device comprising the battery pack.
[0093] Specific examples of the above devices include small devices such as computers, mobile phones, and power tools, and power tools that are powered by an electric motor; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and medium-to-large devices such as power storage devices and power storage systems, but are not limited thereto.
[0094] Since the structure of the battery pack and device, etc., is known in the art, a detailed description thereof is omitted in this specification.
[0095] The following description refers to embodiments of the present invention, but this is for the sake of easier understanding of the present invention and does not limit the scope of the present invention.
[0096] <Example>
[0097] (Separator)
[0098] A coated separation membrane was prepared by dispersing an inorganic material, Al2O3 (Japanese light metal, particle size D50 0.4㎛), a PVDF-based binder, and a dispersant in acetone in a weight ratio of 80:19:1 to prepare a slurry, coating it onto a polyolefin (PO)-based separation membrane (Celgard 2320), and then drying it at a humidity of 30% or higher.
[0099] (cathode)
[0100] An acrylic copolymer was mixed with artificial graphite, carbon black, carboxymethylcellulose, and a binder in a weight ratio of 93:1:1:5 and dispersed in water to prepare a cathode slurry, which was then coated onto a copper current collector and dried and rolled to produce a cathode.
[0101] (Measurement of thickness)
[0102] The thickness (μm) of the above membrane was measured using a contact-type thickness gauge (Mitutoyo VL-50S).
[0103] (Measurement of weight)
[0104] The weight (g) per unit area of the above membrane was measured after cutting the above membrane into 50 mm (width) X 50 mm (length).
[0105] (Manufacturing and measurement of a peeled-off separator)
[0106] The coating layer of the above-mentioned separator was removed using an acetone solvent, and the thickness and weight of the separator from which the coating layer was removed were measured in the same manner as those of the separator.
[0107] (Measurement of adhesive strength)
[0108] The cathode and the separator were laminated so that the porous coating layer of the separator and the cathode faced each other, and then placed between two 100 μm thick polyethylene terephthalate (PET) films and laminated by applying pressure for 1 second at 60°C and 1000 kgf. The obtained product was fixed to an adhesive strength measuring device, LLOYD Instrument, and the upper separator test specimen was peeled at a 180-degree angle at a speed of 25 mm / min at 25°C, and the strength (gf / 25 mm) at that time was measured.
[0109] (Selection of analysis data)
[0110] The thickness of the coating layer alone (Y) was calculated by subtracting the thickness of the membrane from which the coating layer was removed from the total thickness of the membrane. The weight of the coating layer alone was calculated by subtracting the weight of the membrane from which the coating layer was removed from the total weight of the membrane.
[0111] In one embodiment of the present invention, the following data and units were used.
[0112] X : Weight of the coating layer alone per unit area (g / ㎡)
[0113] Y: Thickness of the coating layer only (㎛)
[0114] A: Thickness of the separator excluding the coating layer (㎛)
[0115] B : Density of the coating layer (g / cm³) = Weight of the coating layer alone per unit area (X) (g / m²) / Thickness of the coating layer alone (Y) (㎛)
[0116] Z: Adhesion between separator and electrode (gf / 25 mm)
[0117] In the present invention, a plurality of specimens were prepared and a data set of X, Y, A, B, and Z was measured. It was verified whether the data set satisfied the following two equations (1) and (2).
[0118] 0.6 ≤ Y / A ≤ 0.8 (1)
[0119] 1.4 ≤ B ≤ 1.8 (2)
[0120] FIGS. 2 and FIGS. 3 are analysis results confirming whether data according to one embodiment of the present invention is suitable for the conditions according to the present invention.
[0121] FIG. 2 shows the distribution of data according to condition equation (1) according to one embodiment of the present invention, and FIG. 3 shows the distribution of data according to condition equation (2) according to one embodiment of the present invention.
[0122] Referring to Fig. 2, 465 out of a total of 552 data points satisfy the condition of Equation (1), which corresponds to 84.2%. Referring to Fig. 3, 463 out of a total of 552 data points satisfy the condition of Equation (2), which corresponds to 83.9%. There are 434 data points that simultaneously satisfy the conditions of Equation (1) and Equation (2), which corresponds to 78.6%. The multiple regression analysis below was performed on the data that simultaneously satisfy the conditions of Equation (1) and Equation (2).
[0123] (Multiple Regression Analysis)
[0124] Multiple regression analysis using the following equation (3) was performed on a dataset satisfying the above equations (1) and (2).
[0125] Z = A0 + A1*X + B1*Y + A2*X 2 + B2*Y 2 + C1*X*Y (3)
[0126] Here, Z is the dependent variable representing the adhesion force (gf / 25 mm) between the separator and the electrode, A0, A1, B1, A2, B2, and C1 are parameters, and X (g / m²) and Y (㎛) are independent variables.
[0127] The two-dimensional regression analysis method using Equation (3) used the conventional numerical analysis method. It was confirmed that there is no problem with multicollinearity with the variance inflation factor (VIF) being less than 10 and that the independent variable is related to the dependent variable with a P-value of less than 0.05, and the parameters of Equation (3) were determined by performing multiple regression analysis using the least squares method.
[0128] Equation (3) of the regression analysis results according to the present invention is as follows.
[0129] Z = -2094 + 305*X + 209.4*Y + 28.22*Y 2 - 52.36*X*Y
[0130] X in the above analysis results 2 The parameter of appears as 0, X2 ...was omitted from the formula.
[0131] Figure 4 shows the results of a multiple regression analysis on the adhesion force between a separator and an electrode according to one embodiment of the present invention. As a result of confirming the correlation between the estimated result (Z_measured) and the actual measured value (Z_measured), R 2 It was found that the value was 0.82, indicating a significantly high correlation. Through this, it can be confirmed that the adhesion strength value between the separator and the electrode, which is similar to the actual value, can be indirectly estimated using the estimation method according to the present invention.
[0132] Meanwhile, when using a multiple regression analysis method of this kind, the conditions of the above equations (1) and (2) can be applied to data within the range of the following conditions.
[0133] A range of ±0.1 based on the median of Y / A (4)
[0134] A range of ±0.2 based on the median of B (5)
[0135] A person skilled in the art to which the present invention pertains would be able to perform various applications and modifications within the scope of the present invention based on the above content.
Claims
Claim 1 (S1) a step of measuring X and Y in a separator; (S2) a step of estimating the adhesion force between the separator and the electrode using a correlation equation of X, Y, and the adhesion force between the separator and the electrode; wherein X is the weight of the coating layer alone per unit area in the separator and Y is the thickness of the coating layer alone in the separator. A method for estimating the adhesion force between a separator and an electrode. Claim 2 A method for estimating the adhesion force between a separator and an electrode, wherein measuring X and Y in the separator involves measuring the weight and thickness of the entire separator including the coating layer in the separator, and measuring the weight and thickness of the separator from which the coating layer has been removed, and using the difference therefrom. Claim 3 A method for estimating adhesion between a separator and an electrode, wherein, in claim 1, the separator comprises a separator substrate having a porous structure including a polyolefin-based material and a coating layer including an inorganic material formed on at least one surface of the separator substrate, and the electrode is an anode or a cathode. Claim 4 A method for estimating the adhesion force between a separator and an electrode, wherein, after step (S2), (S3) a step of determining whether there is a defect in adhesion between the separator and the electrode using the adhesion force between the separator and the electrode estimated in step (S2); is added. Claim 5 A method for estimating the adhesion between a separator and an electrode, wherein, prior to step (S2), (S0-1) the adhesion between the separator and the electrode, the adhesion between which the adhesion is to be estimated, the X, and the Y; (S0-2) the step of deriving a correlation equation through multiple regression analysis of the X, the Y, and the adhesion between the separator and the electrode. Claim 6 In claim 5, the above calibration is a method for estimating the adhesion force between the separator and the electrode, which is additionally performed periodically or intermittently. Claim 7 In claim 6, the above additional calibration data replaces conventional calibration data or is a method for estimating the adhesion force between a separator and an electrode that is added to conventional calibration data. Claim 8 A method for estimating the adhesion strength between a separator and an electrode according to claim 5, wherein measuring the adhesion strength between the separator and the electrode involves peeling the separator and the electrode at a 180-degree angle and measuring the peel strength. Claim 9 A method for estimating the adhesion strength between a separator and an electrode according to claim 1, wherein the correlation equation is applied in the range where the value of the thickness of the coating layer only (Y) in the separator and the thickness of the separator excluding the coating layer (A) in the separator is 0.6 to 0.8 and X / Y (g / cm³) is 1.4 to 1.
8. Claim 10 A method for estimating the adhesion force between a separator and an electrode, wherein the correlation equation is applied within a range of ±0.1 from the center value of the thickness of the coating layer only in the separator (Y) / the thickness of the separator excluding the coating layer (A) in the separator, and within a range of ±0.2 from the center value of X / Y (g / cm³). Claim 11 In claim 1, the above correlation equation is the adhesion force between the separator and the electrode = A0 + A1*X + B1*Y + A2*X 2 + B2*Y 2 A method for estimating the adhesion between a separator and an electrode, wherein the parameters A0, A1, B1, A2, B2, and C1 are derived through multiple regression analysis in which X and Y are independent variables and the adhesion between the separator and the electrode is the dependent variable. Claim 12 A method for estimating the adhesion force between a separator and an electrode according to claim 1, wherein the correlation equation is newly derived whenever the separator is changed or the electrode is changed, and the correlation is applied when the correlation is 0.8 or higher.
Citation Information
Patent Citations
Method and device for evaluating membrane electrode assembly
JP2011100641A
Evaluation method of electrode
JP2013062139A
Separator containing organic and inorganic mixture coating layer and battery using the separator
KR101488917B1
Method for measuring adhesion force
KR1020190056781A
Method for performance analysis of secondary battery electrode
KR1020200027693A
